Etymology of the Color in Linguistics (Proceedings of Southern Federal University. Philology, 2021)
DOI 10.18522/1995-0640-2021-1-48-57The article deals with the concept of color in linguistic. There are opinions of scientists who analyzed the concept “shade”. The color must be seen from different points. The article presents the history of the color’s learning. There are some scientists’ points from the different countries. Linguists have opinion that the color in different languages may have the same meaning. There were many scientific experiments, which showed that the color can be a fixed lexeme and can have an alternative equivalent. Other linguists say that the color in different languages cannot have common features. The article emphasizes the need to focus on linguistic and cultural nuances. The color can reflect the culture of the country, man’s mental world. Some linguists underline that the color category is various. The article describes that the visual reception of people consists of the ability to recognize the color. It is impossible to say, what area of men’s interests can be without color. Particular attention is paid to the etymology of colors in the examples. There are many colors, which are very important in the German language.Keywords: color, shade, etymology of the color, linguo-cultural aspect, sociolinguistic dimension.